Activities Of The Internal Affairs Of The USSR Of Uzbekistan In The Years After World War II (Eurasian Journal of Humanities and Social Sciences, 2025)
The article covers the activities of the Ministry of Internal Affairs of the USSR of Uzbekistan after World War II and changes in the internal policy of the Soviet state, including issues of increasing the prestige of the police, combating crime, maintaining public order and strengthening law and order. Issues such as the organizational structure of the police system in the republic in the post-war years, improving personnel skills, introducing new positions in political and educational work, as well as increasing public participation in the fight against crime are discussed